Analysis of Physical, Ocular, and Aquaphobic Properties of Zirconium Oxide Nanofilms by Varying Sputtering Pressure. (6th May 2022) - Kumar, Sujit; Dave, Vikramaditya; Krishnan, Muthamil Bala; Amudha, V.; Gomathi, S.; Soni, Sanjay; Jeelani, Syed Hamim; Subbiah, Ram; Negash, Kassu
Abstract : A thin coating of zirconium oxide (ZrO2 ) is placed on outdoor high-voltage insulators to minimize air fouling. ZrO2 thin film coatings were deposited on glass substrates using a DC sputtering (reactive magnetron) technique with sputtering pressures ranging from 5 to 25 mTorr. Characterization of the deposited films was carried out utilizing approaches such as XRD, AFM, CAG, and spectrophotometer. Following the XRD peaks, when 15 mTorr is reached, the average crystallite size increases, after which it begins to decline. The wettability of the deposited thin layer is associated with the coarseness calculated by AFM. At 15 mTorr pressure, maximum aquaphobic is achieved (107.45°). At this pressure, the transmittance and bandgap were similarly determined to be 90% and 5.43 eV, respectively.